Shaping memories in contemporary narratives - Marta Vignola; Stefano Bory (Funes)
This fourth issue of Funes dedicated to the relationship between memory and narratives is a sort of dialogue among various authors. They tell processes of social construction of memory from different geographical and cultural backgrounds (Chile, Peru, Brazil, Indonesia, Germany, Spain, France, Italy) and through different methodologies. This issue underlines how the circulation in the public sphere of conflicting and unresolved events of the past can take multiple forms through a wide range of communicative, aesthetic and cultural codes. In almost all the contributions, traumatic, silenced, stubborn, insurgent memories are recounted. They try, in a diachronic way, to give back the right to speak to subjectivities and stories often placed on the margins of dominant narratives.